CLINICAL EVALUATION OF EFFICACY OF SHIELD FORCE PLUS VARNISH VERSUS SODIUM FLUORIDE ON CERVICAL DENTIN HYPERSENSITIVITY ON ADULT PATIENTS: A RANDOMIZED CLINICAL TRIAL (Journal of Pharmaceutical Negative Results, 2023)
Aim: This clinical trial was conducted to compare the efficacy of Shield Force Plus Versus sodium fluoride Varnish in the management of hypersensitivity of the cervical area in adult patients for 8weeks.Materials and methods: The study design was two arms, parallel-group, randomized, controlled trial study was conducted on 28 participants with 68 teeth suffering from cervical dentin hypersensitivity received desensitizing agents. Teeth are divided into two groups based on the received treatment (n = 34 for each group): group (1): Shield Force Plus; group (2): sodium fluoride varnish (5%). Dentin hypersensitivity was evaluated by visual analogue scale (VAS) before the agents were applied, 2 minutes after application, after 1, 4 and 8 weeks. For use as hypersensitivity model specimens, dentin discs were prepared from extracted human premolars. The specimens were placed on a fixed device. Following the application of various desensitizer products. After 2 months A scanning electron microscope was used to examine dentinal tubules occlusion of dentin specimens.Results: Regarding (VAS), Intergroup comparison between both materials have shown no statistically significant difference at pre-intervention (P = 0.8432), while after 2 minutes, 1-, 4- and 8-weeks intergroup comparisons revealed statistically significant difference in favour of Shield force plus (P < 0.0001). Intragroup comparison within Shield force plus and NaF have shown statistically significant difference between different follow-up periods (P < 0.0001*). Shield force plus occluded tubules more completely than sodium fluoride varnish.Conclusion: In office desensitizing agents are reliable methods for treatment of dentin hypersensitivity Shield Force is an effective desensitizing agent and provide pain relief which is maintained over time. sodium fluoride in office desensitizing agents. Could provide immediate relief but doesn’t improve by time.